Lymphatic uptake and pharmacokinetics of lipid conjugated brush PEG polymers is altered by interactions with albumin and lipoproteins - Abdallah, Mohammad; Styles, Ian K.; Mörsdorf, Alexander; Grace, James L.; Quinn, John F.; Whittaker, Michael R.; Trevaskis, Natalie L. (Frontiers in Physiology, 2025)
IntroductionIncreased recognition of the role of lymphatics in disease has brought increased focus on the design of lymph-directed delivery systems for imaging agents and therapeutics. Previously, we developed novel brush polyethylene glycol (PEG) polymers functionalized with different lipids and investigated their lymphatic uptake, plasma pharmacokinetics and tissue biodistribution. Diacylglycerol-conjugated brush PEG polymers had enhanced lymphatic uptake and extended plasma elimination half-life after both intravenous (IV) and subcutaneous (SC) administration compared with polymers functionalized with single hydrocarbon chain lipids. These differences in in vivo trafficking were suggested to occur as a consequence of association with endogenous lipid transport pathways, including albumin and lipoproteins. Herein we investigate the impact of pre-mixing the polymers with albumin or high density lipoproteins (HDLs) on their lymphatic uptake, pharmacokinetics and biodistribution, and detail the mechanisms underpinning the polymers in vivo trafficking.MethodsFirst, the impact of pre-mixing diacylglycerol-conjugated PEG polymers (2C12-PEG and 2C18-PEG) with defatted rat serum albumin (RSA) or HDL on the polymers’ IV and SC plasma pharmacokinetics, SC lymph uptake and/or biodistribution was investigated. Next, a mechanistic study confirmed the impact of in situ association of 2C18-PEG with endogenous HDL particles on polymer biodistribution by inhibiting the scavenger receptor class B type 1 (SRB1) receptor before SC dosing 2C18-PEG.ResultsPre-mixing 2C12-PEG with RSA (2C12-PEG/RSA) prolonged the elimination half-life of 2C12-PEG following IV and SC dosing. However, SC lymph transport of 2C12-PEG was reduced by 2C12-PEG/RSA. In contrast, the concentration of 2C18-PEG in plasma, lymph nodes and several tissues increased by pre-mixing with HDL (2C18-PEG/HDL). Unexpectedly, the biodistribution of 2C18-PEG into ipsilateral lymph nodes and adipose tissues at 4 h after dosing was increased in mice pre-dosed with the SRB1 inhibitor, likely due to perturbations in the lipoprotein profile.DiscussionOverall, administration with albumin and altering lipoprotein trafficking pathways modified the biodistribution and lymphatic uptake of the polymers, supporting that they traffic into lymph in association with lipid trafficking pathways. Increasing the association of delivery systems such as lipidated polymers with HDL trafficking pathways could be a viable means to enhance lymphatic uptake of diagnostic and therapeutic agents for lymphatic diseases.